STRATEGI BRANDING SEKOLAH BERBASIS CERAH DALAM MENINGKATKAN DAYA TARIK CALON PESERTA DIDIK DI SDN GIRIPURNO 1 - Umi Nurul Hidayati; Mohamad Joko Susilo (Jurnal Manajemen Pendidikan, 2026)
This study analyzes the branding strategy of SDN Giripurno 1 through the "CERAH" concept (Intelligent, Religious, Adaptive, and Harmonious) to enhance its appeal amidst intense competition with private schools. The research focuses on how a public elementary school builds a distinct identity to address shifting public preferences that prioritize school image and graduate character. Using a descriptive qualitative approach with library research, data were gathered from internal documents, curriculum, and digital publications, then analyzed systematically. The results show that integrating CERAH values into internal, external, and experience branding strategies creates strong institutional differentiation. Consistent communication of these character values significantly boosted public trust and enrollment interest. The originality of this research lies in its exploration of value-based branding within a public school context, an area often overlooked in educational literature. Unlike previous studies focusing on physical facilities, this research demonstrates that the comprehensive institutionalization of character values serves as a strategic magnet, strengthening a school’s competitive position in the modern era.